Bacteriology of deep carious lesions underneath amalgam restorations with different pulp-capping materials - an in vivo analysis - Prasanna Neelakantan; Chandragiri Venkata Subba Rao; Jamuna Indramohan (University of São Paulo, 2012)
Microorganisms remaining in dentin following cavity preparation may induce pulp damage, requiring the use of pulp-capping agents with antimicrobial activity underneath permanent restorations. OBJECTIVE: The aims of this study were to analyze the bacteriological status of carious dentin and to assess the efficacy of different base underneath silver amalgam restorations. MATERIAL AND METHODS: This study was conducted on 50 patients aged 13 to 30 years. Sterile swabs were used to take samples after cavity preparation, which was assessed by microbiological culture to identify the microorganisms present. Following this, cavities were restored with silver amalgam, using one of the materials being investigated, as the base: calcium hydroxide (Group II), polyantibiotic paste (Group III), a novel light-cured fluoride-releasing hydroxyapatite-based liner (Group IV) and mineral trioxide aggregate - MTA (Group V). In Group I, the cavities were restored with silver amalgam, without any base. After 3 months, the amalgam was removed and samples taken again and analyzed for the microbial flora. RESULTS: Lactobacilli were the most commonly isolated microorganisms in the samples of carious dentin. Groups IV and V showed negative culture in the 3-month samples. There was no statistically significant difference between Groups I, II and III. There was no significant difference between Groups IV and V (p>0.05). Both Groups IV and V showed significantly better results when compared to Groups I, II and III (p<0.05). CONCLUSIONS: The hydroxyapatite-based liner and MTA performed significantly better in terms of antibacterial activity than the other materials.